Rancang Bangun Mesin Refill Cat Semprot - Rani Anggrainy; Ahmad Lubi; Mohammad Rizqi Dwi Febrianto; Reynaldi Ramadhan; Ardi Candra Fatkhurrohman; Yunita Sari Yunita Sari; Ferry Budhi Susetyo (Universitas Nasional, 2023)
The big environmental problems faced today are caused by used packaging that is increasingly piling up.Â Unfortunately, not all of this waste can be easily decomposed, one example is used paint cans. The design of this spray paint refill machine aims to reduce paint can waste that is rampant in the community. In addition, this tool also serves to replenish liquid and also compressed air in spray paint cans which can later be reused in the painting process. The spray paint refill machine has a frame size with a length of 275 mm, a width of 250 mm, and a height of 440 mm using hollow iron measuring 20x20 mm which is carried out static load testing on the affected part of the working force of 15 N. Based on the results of static load analysis, it shows that the design of the engine frame is strong enough to withstand the force exerted and the test results of this tool the spray paint refill machine can work optimally and there are no obstacles when filling into the spray paint packaging.